A Novel Surgical Technique for Fixation of Recurrent Acromioclavicular Dislocations: AC Dog Bone Technique in Combination with Autogenous Semitendinosus Tendon Graft - Patrick Holweg; Wolfgang Pichler; Gerald Gruber; Ellen Tackner; Franz Josef Seibert; Patrick Sadoghi; Gloria Hohenberger (Case Reports in Medicine)
Various surgical techniques have been described for the fixation of acromioclavicular (AC) dislocations. However, recurrent dislocation is one of the main complications associated with the majority of these techniques. We report a case of postoperative AC joint redislocation. In order to overcome recurrent dislocation after revision surgery, a reconstruction of the conoid and trapezoid ligament with the use of a free tendon graft in combination with a FiberTape was provided within a novel surgical technique. After 12 months, the patient was very satisfied with the functional outcome. The patient achieved excellent results in the Constant (98 points), SPADI (0 points), and QuickDASH score (0 points). The described technique results in an anatomic reconstruction of the AC joint. The nonrigid nature of the intervention seems to restore the normal arthrokinematics by reconstructing the coracoclavicular ligaments with an autograft which is then protected by the AC Dog Bone artificial ligaments during the healing period. The arthroscopic approach to the AC joint with minimal exposure reduces the risks and complications of the intervention. This is the first case in literature that utilizes the artificial dog bone ligament securing the autograft in an anatomic AC reconstruction.